PEMBATALAN WAKAF DALAM TINJAUAN HUKUM ISLAM - Janiati, Cut (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2022)
Waqf is an Islamic institution that is social in nature, has religious value and serves as a service to Allah SWT. In its function as worship, waqf is expected to be a provision for life in the afterlife. Whereas in its social function as worship, waqf is a very valuable asset in development. Because waqf is worship, its main purpose is devotion to Allah SWT and sincerity for seeking His pleasure. Waqf can be canceled due to the following: a. A blocking event occurred. b. If there is an increase in the waqf property, then the waqf for the excess price, c. Endowment for immoral interests, such as gambling places, prostitution, building churches, buying weapons to kill. d.Waqf to fight fellow Muslim. e. Waqf of infidels for the benefit of Muslims. Meanwhile, the provisions in the review of Islamic law mention the immediate cancellation of waqf. The term and pillars set. If the pillars and conditions are violated by any party, the waqf will automatically be cancelled.